Partition and macronutrients accumulation in pineapple under nitrogen doses and plant density - Souza, Renata Patrícia Dias; Pegoraro, Rodinei Facco; Reis, Sidnei Tavares; Maia, Victor Martins; Sampaio, Regynaldo Arruda (Comunicata Scientiae, 2019)
Studies related to the absorption and exportation capacity of macronutrients by irrigated pineapple are essential for the definition of adequate doses and fertilization management. The objective of this study was to evaluate the accumulation of biomass and macronutrients in the compartments (leaves, shoot, root, seedlings/slip, crown/top, and fruit) of ‘Vitória’ pineapple irrigated in the semiarid region after the use of nitrogen doses and population densities. The treatments, arranged in randomized blocks with three replicates, arranged in a 5x4 factorial scheme, consisted of five nitrogen doses (0, 5, 10, 15 and 20 g per plant) and four population densities (51,282, 76,923, 90,909, and 126,984 plants ha-1). The accumulation of biomass and macronutrients in the pineapple compartments was evaluated at the end of the growing cycle. The increase of N doses combined with the increase of the plant population promoted a linear increase in the accumulation of biomass and macronutrients by the pineapple plants. The leaves presented greater accumulation of macronutrients, followed by the seedlings, shoot, fruit, crown, and roots. The pineapple presented the following decreasing order of macronutrient absorption: K> N> Ca> P> Mg>S. At the dose of 20 g per plant of N and population of 126,984 plants ha-1 were exported from the area by fruits, 1,311 (12%), 150 (9%), 144 (11%), 52 (11%), 46 (12%) and 36 (12%) kg ha-1 of K, N, Ca, P, Mg, and S, respectively; and by the shoots, 2,426 (22%), 480 (29%), 147 (11%), 101 (21%), 67 (18%), and 45 (15%) kg ha-1 of K, N, Ca, P, Mg, and S, respectively.